Development of paper based amperometric biosensor for glucose content measurement in Malaysian Stingless Bee Honey - W. N., Julika; Azilah, Ajit; N., Syazlin; A., Ariff; A., Naila; A. Z., Sulaiman (IOP Publishing, 2020)
Amperometric biosensor for glucose content measurement in Malaysian stingless bee honey was developed using screen printed carbon electrode (SPCE) integrated with paper disc immobilized with enzyme Glucose Oxidase (GOx) using simple physical adsorption method. The paper-based biosensor required only 8 µL of sample solution for glucose analysis. The calibration of glucose biosensor is linear between 0.5 mM to 4.5 mM (R2= 0.9925) and has a detection limit of 0.15 mM. Interference study on several compound affecting the biosensor response and storage stability was investigated. In addition, its performance was demonstrated in the analysis of six honey samples. The results obtained using glucose biosensor was validated by high performance liquid chromatographic (HPLC) method. The addition of glucose in pure honey at various concentration were also tested by this paper-based biosensor where the current obtained shows increasing trend with the addition of glucose. From this research, it can be concluded that, the prototype sensor to determine glucose adulteration in stingless bee honey was successfully developed.